Prognostic value of standard parameters as predictors for long-term renal replacement therapy after liver transplantation - Weigand, Kilian; Bauer, Eva; Encke, Jens; Schmidt, Jan; Stremmel, Wolfgang; Schwenger, Vedat (Nephron. Clinical practice, 2011)
Chronic kidney disease has become increasingly prevalent after liver transplantation (LTPL) because outcome and survival rates have improved. Chronic kidney insufficiency is most likely associated with increased morbidity and mortality. The challenge is to identify patients who will be in need of long-term renal replacement therapy (RRT) after LTPL. We analyzed 208 liver transplant recipients with respect to mortality, associated laboratory values, underlying liver disease, immunosuppressive protocol and the need for RRT. Long-term RRT was defined by the need for RRT 3 months after LTPL. Altogether, 5.8% of the surviving study patients remained in need of RRT 3 months after LTPL. All of these patients continued to need RRT throughout the study period (2 years). The need for RRT significantly increased the 2-year mortality rate 4.3-fold, from 15.4 to 66.7% (p = 0.004). Comparison of laboratory and clinical parameters at the time of LTPL revealed no significant differences for creatinine, albumin and MDRD between patients undergoing hemodialysis 3 months after LTPL and patients without RRT. Comparing mean urea, a difference was observed. However, multivariate regression analyses using easy-to-observe demographic or laboratory parameters failed to generate a model to predict the need for RRT after LTPL. In addition, a comparison of underlying liver disease and immunosuppressive regimes identified no significant differences. Taken together, patients who were on hemodialysis 3 months after LTPL were also on hemodialysis 2 years after LTPL or until death. RRT 3 months after LTPL may predict the risk for chronic renal insufficiency and is associated with significantly increased mortality.
Gesehen am 14.11.2022